1994
DOI: 10.1002/1520-6777(1994)13:3<237::aid-nau1930130305>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Standard and extramural ambulatory urodynamic investigation for the diagnosis of detrusor instability-correlated incontinence and micturition disorders

Abstract: Forty‐six patients were evaluated for complaints of urinary incontinence or voiding disorders. Diagnostic testing included a detailed history, physical examination, urine analysis, and urodynamic studies consisting of a conventional urodynamic test (S.I.) including provocative manocuvers and extramural ambulatory urodynamic monitoring (c.a.m.). We compared the pre‐classificalion diagnoses obtained from the medical history with both urodynamic tests. Conventional cystometry detected detrusor instability in 8 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 7 publications
0
13
0
1
Order By: Relevance
“…This is in agreement with previous reports. Webb et al [1990] found voiding pressures of 79 cm H 2 O with CMG and 107 with AM, and Porru and Usai [1994] noted 75 versus 210 cm H 2 O. High voiding pressures were also recorded in dogs under completely physiological conditions.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This is in agreement with previous reports. Webb et al [1990] found voiding pressures of 79 cm H 2 O with CMG and 107 with AM, and Porru and Usai [1994] noted 75 versus 210 cm H 2 O. High voiding pressures were also recorded in dogs under completely physiological conditions.…”
Section: Discussionmentioning
confidence: 94%
“…In this study we were able to show detrusor instability in 8 of 15 mixed incontinent patients that was not detected by CMG. van Waalwijk van Doorn et al [1991] reported an increased incidence of bladder instability from 18 to 69%, Porru and Usai [1994] reported from 13.3 to 93.7%, Robertson et al [1994] found 38% instability by AM whereas CMG at a filling rate of 100 ml/min showed no instability at all and a filling rate of 50 ml/min detected only 70% of detrusor instability. Porru and Usai [1994] found 18.7% detrusor instability and Bladou et al [1992] detected 19% of uninhibited bladder contractions in women previously diagnosed as having genuine stress incontinence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study reports a sensitivity of 1.00 and specificity of 0.95 for the diagnosis of USI by history taking of stress incontinence symptoms. 171 One study reports an agreement of 93% (USI) and 63% (DO) between the two methods, 172 and one reports an agreement of 60% for the diagnosis of USI.…”
Section: Diagnosis Of Usi and Do In A Mixed Populationmentioning
confidence: 99%
“…AUM over a period of time will detect phasic detrusor activity in symptomatic patients [Webb et al, 1991] in whom the conventional CMG failed to detect any abnormality. A high correlation between symptoms and findings on AUM have been reported by other groups [Webb et al, 1991;Porru and Usai, 1994], which would suggest that this technique more accurately reflects lower urinary tract behavior and therefore symptomatology than its conventional counterpart. Several studies have utilized conventional cystometry in an attempt to demonstrate objective changes in detrusor activity.…”
Section: Discussionmentioning
confidence: 54%